Response of irrigation and fertigation scheduling on flowering, physiological parameters and fruit yield of guava (Psidium guajava L.) under high density planting - Ramniwas, -; Kaushik, R.A.; Sarolia, D.K. (Annals of Agricultural Research, 2014)
An experiment was conducted during 2009-10 and 2010-11 to assess the effect of irrigation and fertigation scheduling on flowering, physiological parameters and fruit yield of 3-years-old guava cv. ’Shweta’ planted at the spacing of 2x1m. The experiment was laid out in factorial randomized block design with sixteen treatment combinations, which included four irrigation levels (basin, 50%, 75% and 100% irrigation of IW/CPE) along with four fertigation levels, viz. basal dose, 50%, 75% and 100% water soluble fertilizers and replicated thrice. From the two years pooled observations it was found that 75% irrigation of IW/CPE (I2) through drip resulted in significantly higher number of flowers per shoot (32.02), fruit set (45.88%), fruit retention (47.83%) and fruit yield of (29.33 t/ha), carbon assimilation rate (5.03 Î¼ mol m-2 s-1) and total chlorophyll content (2.39 mg g-1 fresh weight) in leaf. However, I2 and I3 (100% irrigation of IW/CPE) were at par with each other. Similarly, fertigation level F2 (45, 20, 20 g NPK water soluble fertilizers) showed significantly higher fruit set (44.93%), fruit retention (47.39%), carbon assimilation rate (4.98 Î¼ mol m-2 s-1), total chlorophyll content (2.38 mg g-1 fresh weight), fruit yield (5.96 kg plant-1 & 29.81 t ha-1). Further interaction of irrigation and fertigation levels I3F3, I3F2 and I2F3 and I2F2 were at par with each other and I2F2 level (75% irrigation of IW/CPE + 75% WSF) produced significantly higher fruit set (48.85%) and fruit yield (6.56 kg/ plant & 32.79 t/ha).